The inhibition of inducible nitric oxide production in lipopolysaccharide-stimulated rat macrophages and in silico studies by flavonoids from Iris spuria L. rhizomes. (5th October 2021) - Khallaf, Iman S.A.; Bayoumi, Soad A.L.; Malak, Lourin G.; Hussein, Abeer M.R.; Mohammed, Anber F.; El-Mokhtar, Mohamed A.; Farag, Salwa F.
Abstract: Ethnopharmacological relevance: Iris is the largest genus in the family Iridaceae. Iris plants are distributed in tropical regions of the world. They are used as ornamentals and traditionally used to treat a variety of ailments. Aim: This study aimed to evaluate the anti-inflammatory effect of flavonoids isolated from Iris spuria L. Materials and methods: The isolated flavonoids (1 -4 ) were identified on the basis of different spectroscopic methods (1D- and 2D-NMR) and co-TLC with authentic samples. The anti-inflammatory effect was tested on lipopolysaccharide (LPS)-induced nitric oxide (NO) production from rat-isolated peritoneal macrophages. Modeling and docking simulations of the compounds were performed using Molecular Operating Environment software and the crystal structure of the murine inducible nitric oxide synthase (iNOS). Results: Four flavonoids (1-4 ) had been isolated from the rhizomes of Iris spuria L. (Hocka Hoona) for the first time. They were characterized as 5, 7, 2'-trihydroxy-6-methoxyflavanone (1 ), tectorigenin 7- O - β -D-glucopyranoside (2 ), tectorigenin 4'- O - β -D-glucopyranoside (3 ), and tectorigenin 4'- O -[ β -D-glucopyranosyl(1 → 6)- β -D-glucopyranoside] (4 ). The selective inducible NO synthase inhibitor; aminoguanidine was used as a positive control. The production of nitric oxide (NO) was inhibited in a dose-dependent manner of the isolated compounds along with isoflavonoids (5-9 ) previously isolated from Iris spuria L. (Calizona). A concentration of 60 μg/ml of all tested compounds showed a significant inhibitory effect compared to media with LPS. Molecular modeling experiments supported the obtained biological data. Conclusion: Our results reveal that flavonoids isolated from I . spuria L. (Hocka Hoona) and I. spuria L. (Calizona) appear to have a potential anti-inflammatory effect via inhibition of iNOS. Graphical abstract: Image 1 Highlights: Isolation and identification of flavonoids from I. spuria L. (Hocka Hoona) rhizome. In vitro anti-inflammatory effect of the flavonoids on LPS-induced NO production. Modeling and docking simulations of the isolated flavonoids and iNOS active site.